Development of Quizizz Media for Online Learning for Class IV English Subjects at Madrasah Ibtidaiyah - A. Jauhar Fuad; Khotimatul Khusna (Institut Agama Islam Tribakti Kediri, 2022)
This study aims to determine the feasibility of the media based on the responses of material experts and media experts, as well as to determine student responses to the use of Quizizz media in online learning of English subjects at MI Darul Huda Deyeng. The research method used is a type of Research and Development (R&D) by adapting the Dick and Carrey development model. The test subjects in this study were fourth grade students of MI Darul Huda Deyeng. The data collection instrument used is a questionnaire (questionnaire). The technique used in data collection is a questionnaire with a Likert scale. Analysis of the data used is descriptive analysis. From the results of the research conducted, it shows that the Quizizz media in online learning of class IV English subjects at MI Darul Huda Deyeng which has been developed based on the assessment responses from material experts has obtained a feasibility percentage of 80% and is included in the appropriate category, based on the assessment responses by media experts, it is obtained The percentage of eligibility is 82.66% which is included in the very feasible category, while student responses to the Quizizz media developed get a percentage of 82.82% included in the very feasible category. [Penelitian ini bertujuan untuk mengetahui kelayakan media berdasarkan tanggapan penilaian ahli materi dan ahli media, serta untuk mengetahui respon siswa terhadap penggunaan media Quizizz dalam pembelajaran daring mata pelajaran Bahasa Inggris di MI Darul Huda Deyeng. Metode penelitian yang digunakan merupakan jenis Research and Devlopment (R&D) dengan mengadaptasi model pengembangan Dick and Carrey. Subjek uji coba dalam penelitian ini adalah siswa kelas IV MI Darul Huda Deyeng. Instrumen pengumpulan data yang digunakan yaitu angket (kuisoner). Teknik yang digunakan dalam pengumpulan data yaitu angket dengan skala Likert. Analisa data yang digunakan yaitu analisis deskriptif. Dari hasil penelitian yang dilakukan menunjukkan bahwa media Quizizz dalam pembelajaran daring mata pelajaran Bahasa inggris kelas IV di MI Darul Huda Deyeng yang telah dikembangkan berdasarkan tanggapan penilaian dari ahli materi memperoleh presantase kelayakan 80% dan termasuk dalam kategori layak, berdasarkan tanggapan penilaian oleh ahli media mendapat presentase kelayakan 82,66% yang termasuk dalam kategori sangat layak, sedangkan respon siswa terhadap media Quizizz yang dikembangkan memperoleh presentase 82,82% termasuk dalam kategori sangat layak]